2020
DOI: 10.1136/jech-2020-215097
|View full text |Cite
|
Sign up to set email alerts
|

Racial inequity in fatal US police shootings, 2015–2020

Abstract: IntroductionViolent encounters with police represent a significant cause of morbidity and mortality in the USA, especially among Black, Indigenous, and People of Colour (BIPOC). This study characterises trends in fatal police shootings overall and by armed status and quantifies inequities in mortality burden and years of life lost (YLL) across racial/ethnic groups.MethodsLongitudinal study of Washington Post data on fatal police shootings in the USA using generalised linear-mixed models to capture trends with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 10 publications
1
44
0
Order By: Relevance
“…Few studies have reported on IPV (a construct that includes, but is broader than, intimate partner violence). Furthermore, in spite of evidence showing higher rates of fatal police encounters among Black and Hispanic people before and during the early pandemic, 42 few scientific studies have generated early pandemic estimates for IPV by race/ethnicity or gender. Concordant with our early pandemic estimates for the entire sample (19%) and for White women (16%), a web-based survey of women and men found an 18% overall prevalence of intimate partner violence in April 2020 and reported no difference in worsening intimate partner violence between Hispanic and non-Hispanic respondents.…”
Section: Disparities In Health-related Socioeconomic Risksmentioning
confidence: 99%
“…Few studies have reported on IPV (a construct that includes, but is broader than, intimate partner violence). Furthermore, in spite of evidence showing higher rates of fatal police encounters among Black and Hispanic people before and during the early pandemic, 42 few scientific studies have generated early pandemic estimates for IPV by race/ethnicity or gender. Concordant with our early pandemic estimates for the entire sample (19%) and for White women (16%), a web-based survey of women and men found an 18% overall prevalence of intimate partner violence in April 2020 and reported no difference in worsening intimate partner violence between Hispanic and non-Hispanic respondents.…”
Section: Disparities In Health-related Socioeconomic Risksmentioning
confidence: 99%
“…Native mascots will one day be a thing of the past, but if we do not reject the narratives that allowed these mascots to persist, Native oppression will simply continue in other forms. From the under-investigation of the MMIWG2ST epidemic (Lucchesi & Echo-Hawk, 2018) to the disproportionately high rates of police brutality (Lett et al, 2020), erasing and dehumanizing narratives fuel inequalities that are quite literally a matter of life and death for Natives. Uplifting the full humanity and contemporary significance of Natives requires seeing Natives the way they want to be seen and creating a culture in which Americans both face past moral transgressions and commit to an equitable future for all Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Using this language in the Diversity and Inclusion value, as well as in the mission statement, further marginalizes and belittles the lived experiences of underrepresented individuals. Moreover, there is growing evidence demonstrating that “all” are not well served within broader context of the U.S. criminal justice system, given well-documented issues of bias, structural racism, and white privilege [ [16] , [17] , [18] , [19] , [20] , [21] ]. Any value statement that addresses diversity and inclusion should explicitly recognize the inequities, racism, and biases that hinder the inclusion of underrepresented individuals and offer aspirations (i.e., actionable goals) to remedy such deeply embedded structures maintained by the status quo and adherence to meritocratic processes.…”
Section: Introductionmentioning
confidence: 99%